The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1089/ars.2012.4878
|View full text |Cite
|
Sign up to set email alerts
|

Trapping of Human Hemoglobin by Haptoglobin: Molecular Mechanisms and Clinical Applications

Abstract: A detailed analysis of the influence of Hp glycosylation will be instrumental to generate a deeper understanding of its biological function. Several pathological conditions also modify the glycan compositions allowing Hp to be potentially used as a marker protein for these disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 95 publications
0
27
0
2
Order By: Relevance
“…29 It also has catalytic and antibacterial capacities in controlling the acute-phase response and plays a role as a natural antagonist for receptor-ligand activation in the immune system. 30,31 Haptoglobin is a highly sialylated glycoprotein with four N-glycosylation sites at Asn 184, 207, 211, and 241. 32,33 It has gained considerable attention because of its potential as a signature molecule to display aberrant glycosylation in inflammatory disorders (e.g., liver cirrhosis, pancreatitis) and various types of cancer (e.g., of colon, lung, liver, prostate and pancreas).…”
Section: Introductionmentioning
confidence: 99%
“…29 It also has catalytic and antibacterial capacities in controlling the acute-phase response and plays a role as a natural antagonist for receptor-ligand activation in the immune system. 30,31 Haptoglobin is a highly sialylated glycoprotein with four N-glycosylation sites at Asn 184, 207, 211, and 241. 32,33 It has gained considerable attention because of its potential as a signature molecule to display aberrant glycosylation in inflammatory disorders (e.g., liver cirrhosis, pancreatitis) and various types of cancer (e.g., of colon, lung, liver, prostate and pancreas).…”
Section: Introductionmentioning
confidence: 99%
“…Hp, a major acute-phase glycoprotein comprising 0.4–2.6% of total blood proteins, consists of two α- and two β-subunits whose glycosylation level changes in various types of cancer and inflammation [8, 9]. Hp is a highly sialylated glycoprotein with four N-glycosylation sites in β-chain at Asn 184, 207, 211, and 241 in β-chain [10]. It has been demonstrated that the glycosylated Hp is resulted directly from cancer itself rather than secondary to cancer-induced inflammation [11].…”
Section: Introductionmentioning
confidence: 99%
“…In humans, Hp has a genetic polymorphism that leads to expression of three primary Hp phenotypes that share a common Hb-binding b-chain, yet differ in their a-chain composition (34,42). Hp phenotype 1-1 expresses a smaller a-chain (a1), which can form only one disulfide bond to one other a-b subunit.…”
Section: Introductionmentioning
confidence: 99%